Globalization and contextual factors in accounting the case of Germany - Heidhues, Eva; Patel, Chris (Emerald, 2012)
This research monograph critically examines convergence of financial reporting in Germany by taking into account the influence of political, social and economic factors on accounting. This study makes an original and significant contribution by examining issues and biases in the convergence process that may challenge the assumption of superiority, global comparability and universal applicability of International Financial Reporting Standards. Specifically, this monograph critically evaluates convergence by taking into account German accounting development and examines issues concerning the application of professional judgment, which has increasingly been recognized as an important and controversial topic in international accounting. By applying a holistic approach with an emphasis on multiple perspectives, this study shows that accounting research will be enhanced by a critical examination of contextual environments of countries rather than a focus on measurement, quantification, simplification and categorisation.
Keywords: Business & Economics -- Accounting -- Managerial.; Accounting.; Management accounting & bookkeeping.; Accounting -- Germany.; Comparative accounting.; elektronické knihy; electronic books